Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/inthealth/iht035
|View full text |Cite
|
Sign up to set email alerts
|

Supporting 'medicine at a distance' for delivery of hospital services in war-torn Somalia: how well are we doing?

Abstract: With a support package, satisfactory standards of care were met for hospital care in Somalia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Two studies conducted non-randomised open intervention studies (36,37) . The remaining studies have used a retrospective observational study design (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) , a prospective observational study design (53)(54)(55)(56)(57) four of them were cohort (53)(54)(55)(56) , a pre post design (58)(59)(60)(61) , and one descriptive study (62) .…”
Section: Clinical Outcomementioning
confidence: 99%
“…Two studies conducted non-randomised open intervention studies (36,37) . The remaining studies have used a retrospective observational study design (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) , a prospective observational study design (53)(54)(55)(56)(57) four of them were cohort (53)(54)(55)(56) , a pre post design (58)(59)(60)(61) , and one descriptive study (62) .…”
Section: Clinical Outcomementioning
confidence: 99%
“…20 A participant from Ukraine referring to her study reported the following: 21 This research has shown relatively low levels of HIV testing and re-testing among most at-risk populations. A new testing mechanism called 'self-assisted testing' was developed and introduced in 2015 by HIV/AIDS Alliance Ukraine.…”
Section: Change In Non-government Organisational Policy/practicementioning
confidence: 99%
“…It was stated that there was not enough treatment infrastructure. 28 Due to prolonged periods of conflict and instability, Somalia has turned into an essentially fragile state, destroying existing health infrastructures and preventing effective institutional investments in quality health care. [29][30][31] Although MMFs could be treated in the country through an equipped center developed in Mogadishu with the cooperation of Turkey and Somalia governments, across the country illiteracy is still a major health problem.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,12,14,16,17,24,26,27 Depending on the shape and severity of the current trauma, the treatment of MFFs by applying debridement and suture, open surgical approach, and osteosynthesis þ/À internal fixation has improved well in the past few decades with the development of materials and technology. 5,9,14,28 Open reduction procedures, satisfactory facial aesthetics, early preservation of functions, and reduction in the incidence of complications can be achieved. 4,9 Besides, the treatment of MFFs varies among surgeons depending on the instrument 9 and continues to be a challenge in developing countries due to the limited resources and sufficient skill requirements.…”
mentioning
confidence: 99%